Social Sciences : Emergence and Scope - Ranganathan, S. R. (Journal of Information and Knowledge, 1972)
The emergence of "Social Sciences" as a subject is traced with the aid of two standard dictionaries, a few standard schemes for library classification, two standard encyclopaedias, and a standard documentation serial. The scope of the subject "Social Sciences" is examined with the aid of the schemes for library classification, encyclopaedias and dictionaries. Lastly the propriety of using the term ’ Sciences’ is examined and confirmed with the aid of the Spiral of Scientific Method.